Kulturtradierung in geisteswissenschaftlichen Fächern Eine rekonstruktive Studie zu epistemologischen Überzeugungen von Lehrkräften - Rau, Caroline (Studien zur Professionsforschung und Lehrerbildung, 2020)
This study examines the epistemological beliefs of humanities teachers. It aims to describe how they construct knowledge in the humanities and to identify associated forms of cultural transmissions. How do teachers deal with cultural manifestations such as poems or images in their teaching practice? How is their meaning elaborated? Which meanings are given? The methodology of the study is based on the qualitative-reconstructive research paradigm: The data were collected by group discussions and analysed using the documentary method. The epistemological beliefs of humanities teachers show that teacher transmit culture as high culture. They understand a cultural canon in dimension of the nation state. Teachers tend to limit the significance and the potential meaning of cultural content in school practice by introducing into a today problematic cultural essentialism. In reconstructing their epistemological beliefs, it also became obvious that these beliefs affect the reception of culture: The reproduction of traditional cultural content or its meaning is the focus. Students are denied the opportunity to influence culture(s) and, if necessary, to transform culture by cultural production. The study contributes to empirical education research, to subject didactics in the humanities and to the foundations in education. This study has opened up new perspectives on a subject that has previously been the topic of relatively little research, thus making a valuable contribution to basic research in teaching of the humanities. (DIPF/Orig.)